1997
DOI: 10.1111/j.1600-0668.1997.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Indoor Air Quality in Schools in Relation to Exposure

Abstract: This paper presents data on indoor air quality in schools as perceived by those working in them and relates these data to exposure measurements. Data on subjective air quality, domestic exposures and health aspects were gathered by means of a questionnaire which was sent to all personnel in 38 schools; it was completed by 1410 persons (85’4 of the total). Data on exposure were gathered by exposure measurements in classrooms. The results indicate that 53% of the personnel perceived the indoor air quality as bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 26 publications
6
73
5
Order By: Relevance
“…It was reported that, the concentration of formaldehyde was below the detection limit (<10 g/m 3 ) and the mean indoor Total VOC (TVOC) concentrations ranged from 70 to 180 g/m 3 . VOCs were investigated in randomly selected 38 public schools (96 classrooms) by Smedje et al (1997). Formaldehyde was below the detection limit of 5 g/m 3 , the mean sum of 14 identified VOCs was 35 g/m 3 , and the highest concentrations were of limonene, n-decane, toluene, and xylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that, the concentration of formaldehyde was below the detection limit (<10 g/m 3 ) and the mean indoor Total VOC (TVOC) concentrations ranged from 70 to 180 g/m 3 . VOCs were investigated in randomly selected 38 public schools (96 classrooms) by Smedje et al (1997). Formaldehyde was below the detection limit of 5 g/m 3 , the mean sum of 14 identified VOCs was 35 g/m 3 , and the highest concentrations were of limonene, n-decane, toluene, and xylene.…”
Section: Introductionmentioning
confidence: 99%
“…The other component, the contaminant concentrations, is also important because volatile organic compounds (VOCs) are ubiquitous in the environment since there are many sources (e.g., traffic and industrial emissions as outdoor sources, building and furnishing materials, arts and crafts materials, cleaning agents, and personal care products as indoor sources) (Sexton et al, 2007;Shendell et al, 2004). There are also other factors that influence indoor air quality: schools are commonly associated with high population density, poor ventilation, lack of maintenance, and unsatisfactory cleaning (Daisey et al, 2003;Smedje et al, 1997). School children are more sensitive to environmental pollutants than adults, because of their higher breathing rate relative to their body size, and continuing growth (Faustman et al, 2000), which translate into higher healthrisk levels.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous school studies, we have demonstrated a relationship between settled dust and the perception of air quality (10). To our knowledge, little information is available on the relation between clinical signs on one hand, and cleaning routines or settled dust contamination in schools on the other.…”
mentioning
confidence: 99%
“…The levels in one classroom was more than 2500 ppm CO 2 , 73% of the time while the level of CO 2 stood at 1100 ppm in another room, when the school began during the day. Smedje et al [18,19] recounted the mean and ranges of indoor CO 2 intensities for 96 classrooms in 38 Swedish schools that were chosen randomly from a populace of 130 schools; 61% of these schools boasted of automatic supply and exhaust air systems while the rest had natural ventilation. The intensities were aggregated to be around 990 ppm CO 2 for 38 schools, but surpassed 1000 ppm for 41% of the calculations (maximum = 2800 ppm).…”
Section: Co 2 Intensitiesmentioning
confidence: 99%